Menu planning practices in early childhood education and care – factors associated with menu compliance with sector dietary guidelines. (27th August 2019) - Grady, Alice; Stacey, Fiona; Seward, Kirsty; Finch, Meghan; Jones, Jannah; Yoong, Sze Lin
Abstract: Issue addressed: Despite recommendations, early childhood education and care services do not plan menus in accordance with sector dietary guidelines. This study aimed to examine the following among Australian long day care services: (a) menu planning practices; (b) prevalence of menu compliance with sector dietary guidelines; and (c) menu planning practices associated with higher menu compliance with sector dietary guidelines. Methods: Long day care services within Hunter New England, NSW participated in a pen and paper survey assessing menu planning practices and socio‐demographic and service characteristics. Two‐week menus were assessed for compliance with sector dietary guidelines, based on the number of servings of food groups and discretionary foods provided per child, per day. Results: Staff from 72 services completed the survey and 69 provided their menu. Results indicated the service cook was fully responsible for planning the menu in 43% of services, and 57% had received written support to assist with menu planning. Service menus were compliant with an average of 0.68 out of six food groups and discretionary foods. In poisson regression models, a shorter menu cycle length ( P  = .04) and the receipt of training opportunities to support menu planning ( P  < .01) were significantly associated with higher menu compliance. Conclusions: Menu compliance with sector dietary guidelines is low among participating long day care services. So what?: The implementation of practices such as shortening of the menu cycle and the provision of training opportunities may assist in the planning of menus that are more compliant with dietary guidelines in this setting.